FRI0420 Long term inhibition of IL-17a with secukinumab reduces spinal inflammation but has no influence on fatty lesions as assessed by magnetic resonance imaging in patients with ankylosing spondylitis. (23rd January 2014) - Baraliakos, X.; Braun, J.; Laurent, D.; Baeten, D.; van der Heijde, D.; Sieper, J.; Emery, P.; McInnes, I.; van Laar, J.; Landewe, R.; Wordsworth, P.; Wollenhaupt, J.; et al.
Abstract : Background: Secukinumab (fully human IgG1k anti-IL17A monoclonal antibody) significantly improved clinical signs and symptoms of active ankylosing spondylitis (AS) patients enrolled in a recent proof-of-concept (PoC) study. Magnetic resonance images (MRI) of these patients (pts) showed reduction of spinal inflammation at week (W) 6 and W28 after initiation of treatment. Objectives: To evaluate a subgroup of pts (N=13) in the open label extension study, who had MRI assessments at baseline (BL), W28 and W94. Methods: In the 28W PoC study, 27/30 pts had sequential MRI studies, 22 had received secukinumab 2x10 mg/kg administered intravenously 3 Ws apart, and 5 pts had been randomised to placebo. 20 patients entered the extension study, 13 having MRI data at W94. Of these 13, ten were treated with secukinumab and 3 with placebo in the core study. In the extension study, all received secukinumab 14x3 mg/kg administered 4 Ws apart. MRIs (T1 and STIR) were rescored for this study. ASspiMRI-a scores and the occurrence of vertebral edges (VE) inflammatory and fatty lesions were evaluated by an independent blinded reader. Results: All 13 pts completed this exploratory MRI substudy. In pts receiving 2x10 mg/kg secukinumab followed by 14x3 mg/kg (n=10) secukinumab, spinal inflammation was reduced compared to BL at W28 –similar to the results of the core study– and this reduction was sustained up to W94 (Fig 1 ). Also in 3 pts who had initially received placebo switching to secukinumab at W28, MRI inflammation at W94 was reduced. Of the 920 VEs evaluated, the proportion of VEs with inflammatory lesions was reduced from 9.9% (n=91) at BL to 3.7% (n=34) at W28 and 3.6% (n=33) at W94. In contrast, the proportion of fatty lesions at BL (13.5%, n=124) remained largely unchanged at W28 (14.3%, n=132) and W94 (13.7%, n=126). Image/graph: Conclusions: MRI analysis suggests that the IL-17 inhibitor secukinumab may reduce spinal inflammation and this effect may be sustained for up to 2 years, using a lower maintenance dose compared to the induction regimen. Notably, secukinumab appeared not to have any influence on fatty lesions. This observation contrasts recent reports of AS pts treated with TNF-blockers. The potential impact of these preliminary findings on radiographic progression under secukinumab therapy will be studied in larger trials. Disclosure of Interest: X. Baraliakos: None Declared, J. Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, UCB, Consultant for: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, UCB, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB, D. Laurent Shareholder of: Novartis, Employee of: Novartis, D. Baeten Grant/research support from: Abbott, MSD, Pfizer, Centocor, Jansen, Novartis, UCB, Eli Lilly, Boehringer, Roche, BMS., Consultant for: Abbott, MSD, Pfizer, Centocor, Jansen, Novartis, UCB, Eli Lilly, Boehringer, Roche, BMS., D. van der Heijde Grant/research support from: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Chugai, Daiichi, Eli-Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Vertex, Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Chugai, Daiichi, Eli-Lilly, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer, Roche, Sanofi-Aventis, Schering-Plough, UCB, Vertex, Employee of: Director of Imaging Rheumatology bv, J. Sieper Consultant for: Novartis, P. Emery: None Declared, I. McInnes Consultant for: Novartis, J. van Laar: None Declared, R. Landewe Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Rhoche, Schering-Plough, UCB, Wyeth, Consultant for: Abbott, Ablynx, Amgen, Astra-Zeneca, Bristol Myers Squibb, Centocor, Glaxo-Smith-Kline, Novartis, Merck, Pfizer, Rhoche, Schering-Plough, UCB, Wyeth, Employee of: director of Rheumatology Consultancy BV, Speakers bureau: Abbott, Amgen, Bristol Myers Squibb, Centocor, Merck, Pfizer, Rhoche, Schering-Plough, UCB, Wyeth, P. Wordsworth: None Declared, J. Wollenhaupt: None Declared, H. Kellner: None Declared, A. Wright Shareholder of: Novartis, Employee of: Novartis, F. Vandenhende: None Declared, K. Radford Employee of: Novartis contractor, B. Borah Employee of: Novartis, W. Hueber Shareholder of: Novartis, Employee of: Novartis